2007
DOI: 10.1002/glia.20513
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin potently enhances swelling‐sensitive glutamate efflux from cultured astrocytes

Abstract: High concentrations of thrombin (Thr) have been linked to neuronal damage in cerebral ischemia and traumatic brain injury. In the present study we found that Thr markedly enhanced swelling-activated efflux of (3)H-glutamate from cultured astrocytes exposed to hyposmotic medium. Thr (0.5-5 U/mL) elicited small (3)H-glutamate efflux under isosmotic conditions and increased the hyposmotic glutamate efflux by 5- to 10-fold, the maximum effect being observed at 15% osmolarity reduction. These Thr effects involve it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
63
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 33 publications
(52 reference statements)
9
63
0
Order By: Relevance
“…Another possibility is that ER-related proteins may be expressed in gliomas and may mediate the response to tamoxifen (51). Finally, especially at high doses, tamoxifen might act independently of any steroid receptor by influencing calmodulin (78), various kinases (70), or intracellular calcium (79), or through other mechanisms (80). A number of studies indicate that inhibition of cell proliferation in gliomas by tamoxifen seems to operate…”
Section: Actions Of Steroid Hormone Receptor Agonists and Antagonistsmentioning
confidence: 99%
“…Another possibility is that ER-related proteins may be expressed in gliomas and may mediate the response to tamoxifen (51). Finally, especially at high doses, tamoxifen might act independently of any steroid receptor by influencing calmodulin (78), various kinases (70), or intracellular calcium (79), or through other mechanisms (80). A number of studies indicate that inhibition of cell proliferation in gliomas by tamoxifen seems to operate…”
Section: Actions Of Steroid Hormone Receptor Agonists and Antagonistsmentioning
confidence: 99%
“…Several recent in vitro studies have found that a number ob substances, which are produced ore released in ischemia, such as reactive oxygen species H 2 O 2 , reactive nitrogen species peroxynitrite, thrombin, and ATP, all drastically increase swelling-activated glutamate release from moderately swollen astrocytes [69][70][71][72].…”
Section: Volume-regulated Anion Channels and The Reversed Mode Of Glumentioning
confidence: 99%
“…In this context, we and others Kimelberg, 2002, 2005;Heacock et al, 2004Heacock et al, , 2006Cheema et al, 2005Cheema et al, , 2007Ramos-Mandujano et al, 2007) have recently demonstrated that the volume-dependent release of osmolytes from a variety of neural cells can be dramatically enhanced following activation of certain G-protein-coupled receptors. Receptor activation not only increases the extent of osmolyte release, but it also lowers the threshold osmolarity ("set-point") at which osmolytes are released, thereby permitting cells to respond to small, physiologically relevant, reductions in osmolarity.…”
mentioning
confidence: 81%